Income inequality in developing countries: Fiscal policy's role amid uncertainty - Léleng Kebalo; Stéphane Zouri (Journal of Applied Economics, 2024)
This study investigates the impact of uncertainty on income inequality in developing countries. Unlike prior studies, we analyse the role that the fiscal policy could play in the relationship. Using a sample of 66 developing countries over the period 2000-2020, we find at several levels of robustness that, uncertainty increases income inequality in developing countries, especially those with fiscal deficits and less fiscally disciplined. Additionally, we find that fiscal surpluses mitigate the negative effects of uncertainty on wealth distribution which in turn reduces income inequality. This result reveals the socio-economic stabilizing role that fiscal policy management could play during periods of uncertainty. Fiscal policy can maintain and enhance economic stability when countries face certain uncertainty.
Keywords: 330; developing countries; fiscal policy; Income inequality; uncertainty